Transparency Information Website-Based Regional Finance Throughout Government Districts and Cities in Jambi Province in 2016-2018 - Zulfa, Atifa; Yudi, Yudi; Rahayu, Rahayu (Faculty of Economics and Business Universitas Jambi, 2024)
This study aims to measure the level of transparency of regional financial information in Jambi Province by reviewing three main aspects, namely planning, implementation, and budget reporting and accountability. The study was conducted on 11 official local government websites in Jambi Province with an observation period from 2016 to 2018. The method used was quantitative descriptive with secondary data sources obtained through literature study and observation. Data analysis referred to four main criteria, namely availability, accessibility, timeliness, and frequency of information disclosure, as developed by Huwae (2016), and categorized according to the Open Budget Index (OBI) standards. The results of the study show that all local governments in Jambi Province are in the category of inadequate transparency. Most regions are in the Scant or None category, while a small number are in the Minimal category. This indicates that transparency is not yet a top priority in local financial management in Jambi Province. These findings are expected to serve as evaluation material and input for local governments in improving the transparency of public financial information through online media in a consistent and sustainable manner.